Future of Farming - Polyhouse Farming - Singla, Rachna; Singh, Jasvinder (Journal of Agricultural Extension Management, 2018)
The adverse effects of the green revolution on soil fertility, emergence of new insect pests and diseases and declining water table level have tempted the farmers to consider alternate methods of cultivation which could curb the adverse effects and provide an opportunity to grow crops throughout the year. Protected Cultivation Technology was one such alternative which seemed promising to the farmers. Based on this, Krishi Vigyan Kendra, Patiala conducted training for growers and end-users on the use of complete technology for protected cultivation of high-value vegetables and flowers, including IPM, post-harvest handling, on-farm value-addition, packaging, etc. and marketing. By adopting hi-tech farming practices, Mr. Meharban Singh, a farmer, has become an icon for other farmers of the region. His adoption of modern practices is very rewarding both economically and socially. He is very satisfied with the technological intervention. Judicious use of pesticides on his vegetables has helped him in getting a good price in the market and has enabled him to create a niche for himself. Other farmers of the adjoining areas often seek guidance from him regarding cultivation of vegetables etc. and he personally encourages them to adopt crop diversification as a means to conserve the environment and increase income.